Air cholangiography in endoscopic bilateral stent-in-stent placement of metallic stents for malignant hilar biliary obstruction. (March 2016) - Lee, Jae Min; Lee, Sang Hyub; Jang, Dong Kee; Chung, Kwang Hyun; Park, Jin Myung; Paik, Woo Hyun; Lee, Jun Kyu; Ryu, Ji Kon; Kim, Yong-Tae
Background: Although endoscopic bilateral stent-in-stent (SIS) placement of self-expandable metallic stents (SEMS) is one of the major palliative treatments for unresectable malignant hilar biliary obstruction, post-endoscopic retrograde cholangiopancreatography (ERCP) cholangitis can occur frequently due to inadequate drainage, especially after contrast injection into the biliary tree. The aim of this study is to evaluate the efficacy and safety of air cholangiography-assisted stenting. Methods: This study included 47 patients with malignant hilar biliary obstruction who underwent endoscopic bilateral SEMS placement using the SIS technique. They were divided into two groups, air ( n = 23) or iodine contrast ( n = 24) cholangiography. We retrospectively compared comprehensive clinical and laboratory data of both groups. Results: There were no significant differences found between the two groups with respect to technical success (87% versus 87.5%, air versus contrast group, respectively), functional success (95% versus 95.2%), 30-day mortality (8.3% versus 8.7%) and stent patency. Post-ERCP adverse events occurred in 5 (21.7%) of the patients in the air group and 8 (33.3%) of the patients in the contrast group. Among these, the rate of cholangitis was significantly lower in the air group (4.8% versus 29.2%, p = 0.048). In multivariate analysis, air cholangiography, technical success and a shorter procedure time were significantly associated with a lower incidence of post-ERCP cholangitis. Conclusions: Air cholangiography-assisted stenting can be a safe and effective method for endoscopic bilateral SIS placement of SEMS in patients with malignant hilar biliary obstruction.